Coping in a Bilingual Community: Sixth Graders in Châteauguay, Québec - Hubbell, Linda J. (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1981)
As part of a larger study of bilingual and monolingual children in Châteauguay, Québec, interviews were conducted with Grade 6 students from five types of home and school language backgrounds to compare their varying view of their own linguistic competence in confronting a world of two languages. Questions focussed on their self perceptions of their skills in English and French, their past experiences in both languages, and their reactions to real-life and hypothetical situations. Results were discouraging in that children of all five backgrounds report intermixing without interacting.